2008
DOI: 10.1007/s11064-008-9677-x
|View full text |Cite
|
Sign up to set email alerts
|

Electro-acupuncture Reduces Neuronal Apoptosis Linked to Bax and Bcl-2 Expression in the Spinal Cords of Cats Subjected to Partial Dorsal Root Ganglionectomy

Abstract: While electro-acupuncture (EA) has been well known to contribute towards neuroplasticity occurring in both the central and the peripheral nervous system after injury, the underlying mechanism remains largely unknown. This study evaluated the effects and the possible mechanism of EA on neuronal apoptosis in the spinal cords of cats subjected to the removal of L(1)-L(5) and L(7)-S(2) dorsal root ganglion, sparing the L(6) dorsal root ganglion. EA treatment decreased the number of TUNEL-positive apoptotic cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
2
5
0
3
Order By: Relevance
“…28 Previous study reported that EA treatment reduced neuronal apoptosis through decreasing Bax and increasing Bcl-2 expression in the spinal cords of cats following partial resection of dorsal root ganglion. 29 In line with previous studies, our study showed that L-OHP significantly increased Bax/ Bcl-2 ratio in sciatic nerve of rats 14 days after establishing OIPN models, which was reversed by EA treatment. Furthermore, one of the main functions of GR-α is the induction of apoptosis, either by inhibiting the expression of the Bcl-2 or by increasing the expression of Bax.…”
Section: Discussionsupporting
confidence: 92%
“…28 Previous study reported that EA treatment reduced neuronal apoptosis through decreasing Bax and increasing Bcl-2 expression in the spinal cords of cats following partial resection of dorsal root ganglion. 29 In line with previous studies, our study showed that L-OHP significantly increased Bax/ Bcl-2 ratio in sciatic nerve of rats 14 days after establishing OIPN models, which was reversed by EA treatment. Furthermore, one of the main functions of GR-α is the induction of apoptosis, either by inhibiting the expression of the Bcl-2 or by increasing the expression of Bax.…”
Section: Discussionsupporting
confidence: 92%
“…29) Bcl-2 and Bcl-w is widely expressed in mammalian tissues, including the central nervous system, and functions as a negative regulator of neuronal apoptosis. 30) Neural expression of Bcl-2 is highest in the mature brain, suggesting that Bcl-2 function may be particularly important in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Cats in groups IV, V were subjected to 7, 14 days of EA treatment at two paired acupoints, zusanli-xuanzhong and futu-sanyinjiao [11]. As shown in Fig.…”
Section: Electro-acupuncturementioning
confidence: 99%